Challenges of Universal Adoption of The Budapest Convention on Cybercrime - Azmi, Agus Nilmada; Shabrina, Syarah (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2023)
This research analyses the challenges of universal adoption of the Budapest Convention on Cybercrime. The development of scienceand technology has experienced a very rapid movement that cannot be separated from its negative implications. One of them is theemergence of cybercrime attacks, or cybercrimes that utilize all loopholes and tricks on the sidelines of technological advances.Cybercrime has evolved into a transnational or international crime. The Budapest Convention on Cybercrime is an internationaltreaty that governs matters related to cybercrime. Most countries in the world have adopted and ratified it, but some countries, suchas Russia, India, and Brazil, have chosen not to. This study seeks to identify the challenges faced in adopting the universal BudapestConvention. This study used qualitative-descriptive methods using observational data, literature, and documents related to thechallenges faced in the universal adoption of the Budapest Convention. This challenge is faced by the Council of Europe as the initiatorof this convention by creating an agenda to realize the universal adoption of the Budapest Convention in order to take it into accountand overcome it, especially related to combating cybercrime.Keyword: Budapest Convention; Cybercrime; Adoption